2017
DOI: 10.1016/j.mcn.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determinants of the Caenhorhabditis elegans dopamine transporter dictating in vivo axonal export and synaptic localization

Abstract: The monoamine neurotransmitter dopamine (DA) acts across phylogeny to modulate both simple and complex behaviors. The presynaptic DA transporter (DAT) is a major determinant of DA signaling capacity in ensuring efficient extracellular DA clearance. In humans, DAT is also a major target for prescribed and abused psychostimulants. Multiple structural determinants of DAT function and regulation have been defined, though largely these findings have arisen from heterologous expression or ex vivo cell culture studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…In fact, we recently identified a compound with pharmacochaperoning activity by analyzing a series of partial substrates ( 49 ). Second, the current study shows that D. melanogaster can be used as a model system to test candidate pharmacochaperones within a reasonable time frame; Caenorhabditis elegans is also being explored as an alternative model organism ( 50 , 51 ). Third, an additional class of compounds can be envisaged by analogy with the cystic fibrosis transmembrane conductance regulator (CFTR/ABCC7), where the corrector lumacaftor remedies the folding deficiency of some mutants ( 52 ) and the potentiator ivacaftor potentiates the action of cAMP on channel gating and thus enhances their Cl − conductance ( 53 ).…”
Section: Discussionmentioning
confidence: 96%
“…In fact, we recently identified a compound with pharmacochaperoning activity by analyzing a series of partial substrates ( 49 ). Second, the current study shows that D. melanogaster can be used as a model system to test candidate pharmacochaperones within a reasonable time frame; Caenorhabditis elegans is also being explored as an alternative model organism ( 50 , 51 ). Third, an additional class of compounds can be envisaged by analogy with the cystic fibrosis transmembrane conductance regulator (CFTR/ABCC7), where the corrector lumacaftor remedies the folding deficiency of some mutants ( 52 ) and the potentiator ivacaftor potentiates the action of cAMP on channel gating and thus enhances their Cl − conductance ( 53 ).…”
Section: Discussionmentioning
confidence: 96%
“…Supporting the role of SEC24-mediated ER export in DAT axonal targeting, siRNA knockdown against SEC24D in heterologous cell lines slows down dopamine reuptake 106 . In C. elegans , deletion or mutagenesis of a conserved sequence 591 PYRKR 595 in the DAT-1 C′-terminus leads to somatic retention 107 . The PYRKR sequence contains a 3 R motif that mediates the interaction between SEC24 and α2β-adrenergic receptor 107 , 108 , suggesting the failure of DAT-1 synaptic localization might be due to reduced interaction with SEC24-1.…”
Section: Dat Axonal Targetingmentioning
confidence: 99%
“…In C. elegans , deletion or mutagenesis of a conserved sequence 591 PYRKR 595 in the DAT-1 C′-terminus leads to somatic retention 107 . The PYRKR sequence contains a 3 R motif that mediates the interaction between SEC24 and α2β-adrenergic receptor 107 , 108 , suggesting the failure of DAT-1 synaptic localization might be due to reduced interaction with SEC24-1. In HEK293 cells, mutation of the corresponding sequence in DAT does not affect its interaction with SEC24D, nor significantly reduces DAT surface expression, but does disrupt the ability of SEC24D to enhance DAT surface expression 107 .…”
Section: Dat Axonal Targetingmentioning
confidence: 99%
“…One possibility for the incomplete ability of GFP::DAT1 to rescue the Swip of vt34 animals is an impact of the vt34 mutation on transporter trafficking, limiting export of the fusion protein to synapses. Indeed, our prior imaging studies [20, 42] demonstrated perturbed synaptic trafficking of C-terminal truncations of GFP:DAT that also fail to rescue the Swip and 6-OHDA insensitivity of dat-1 mutants. As previously described, quantitation of the distribution of GFP:DAT-1 in N2 head DA neurons demonstrates that expression of GFP::DAT-1 is highest in synapses, followed by the cell soma and then in dendrites (Fig 2C and 2D).…”
Section: Resultsmentioning
confidence: 99%